2014
DOI: 10.1007/s13197-014-1449-9
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical water extraction and antioxidant activity evaluation with on-line HPLC-ABTS·+ assay of phenolic compounds from marigold (Tagetes erecta L.) flower residues

Abstract: Subcritical water extraction (SWE) of phenolics was investigated from marigold (Tagetes erecta L.) flower residues. The total phenolics content (TPC), total flavonoids content (TFC) and antioxidant capacities of extracts were determined, furthermore, antioxidant activities of individual compounds were evaluated with on-line HPLC-ABTS(•+) system. The optimum SWE time was 45 min, solid-to-liquid ratio was 1:50, and the highest TPC and TFC were obtained at 220 °C respectively. The effect of SWE temperature on TPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…The content of quercetagetin in the crude marigold residues extract was 62.8 %, and more than 8 antioxidant compounds were detected in our preciously studies (Gong et al 2012b;Xu et al 2014). In present study, we focused on recovering the major bioactive compound, quercetagetin in the ethanolic extract.…”
Section: Identification Of the Compoundsmentioning
confidence: 97%
See 1 more Smart Citation
“…The content of quercetagetin in the crude marigold residues extract was 62.8 %, and more than 8 antioxidant compounds were detected in our preciously studies (Gong et al 2012b;Xu et al 2014). In present study, we focused on recovering the major bioactive compound, quercetagetin in the ethanolic extract.…”
Section: Identification Of the Compoundsmentioning
confidence: 97%
“…1). There are many reports focused on its antioxidant activity (Gong et al 2012a, b;Xu et al 2014), antiinflammatory activity (Kang et al 2013) and copigment effect (Xu et al 2015). Some scientific researches reported that quercetin has strong inhibition of α-glucosidase, α-amylase and lipase (Dong et al 2012;You et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Usually, extraction temperatures of 80-150°C and extraction times of 1-60 min have been used to extract phenolic compounds by PHWE (see Table 3). In many works, a higher antioxidant capacity has been observed in the extracts obtained at temperatures of over 175°C and at longer extraction times, compared to the extracts obtained at lower temperature and shorter extraction times [36,37,[57][58][59][60][61]. In many of these studies, only the total phenolic compounds and the total antioxidant capacity were measured, with drawbacks as discussed above.…”
Section: Phwe Of Phenolic Compoundsmentioning
confidence: 99%
“…These include extraction from mango leaves [21], pomegranate [22], rice bran [23], potato peel [24], cinnamon [26], citrus pomaces [27], golden oyster mushroom [28], oregano [30], and marigold flowers [31]. These studies have indicated that SWE is a promising technique for the successful preparation and isolation of phenolic compounds from the matrices of various plants.…”
Section: Extraction Of Bioactive Compounds From Plantsmentioning
confidence: 99%